Role of potassium on enzymatic and non-enzymatic antioxidant activities in maize plants growing under drought and hydrogen peroxide stresses - I. K. AL- Samerria; A. K. Abdullah; H. S. Rahi (Journal of Madenat Alelem University College, 2014)
The experiment was carried out in the field, department of field crops, college of agriculture, university of Baghdad during season 2011 to study the effect of interaction of water stress and hydrogen peroxide and potassium on the activity of antioxidant enzyme and non enzyme on maize plant cultivar Bohooth 106 Included studying three levels of water stresses of 40, 60 and 80% of the available water (D1 , D2 and D3), respectively. Three levels of hydrogen peroxide of concentrations (0, 15 and 30 Mm), and foliar application of potassium at concentration of 3000 mg K. L-1 K2SO4 without applied potassium, split–split with RCBD design with three replications was used. The results showed that water stress (D3) and H2O2 (30) Mm significantly increased the antioxidant enzyme activities, superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) and non-enzymatic vitamin C, carotenoid significantly reduced other plant properties of the studied compared with group that not contain a potassium.